Students Perception on Disney Animated Movies as Self-Directed Vocabulary Learning Media - Selma Seila Amelia Putri Swarno; Sofkhatin Khumaidah (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
The integration of digital media in English language learning has provided new opportunities to support students’ vocabulary development, particularly through audio-visual materials. One potential medium is Disney animated movies, which offer authentic language use, visual context, and engaging storylines. This study aims to explore students’ perceptions on Disney animated movies as self-directed vocabulary learning media. A descriptive qualitative approach was employed involving 22 ninth-grade students of MTsN 2 Jember. Data were collected through classroom observations, open-ended questionnaires, and semi-structured interviews. The data were analyzed using the Miles, Huberman, and Saldana model, consisting of data reduction, data display, and conclusion drawing, supported by technique and source triangulation. The findings reveal that students generally hold positive perceptions of Disney animated movies, perceiving them as interesting, enjoyable, easily accessible, and helpful in understanding vocabulary through visual context, improving pronunciation, increasing learning motivation, and supporting independent learning. However, several negative perceptions were also identified, including difficulties in understanding fast-spoken dialogues, reliance on subtitles, limited focus due to distractions, and technical problems such as unstable internet connections and unclear audio quality. This study concludes that Disney animated movies have strong potential as self-directed vocabulary learning media when accompanied by appropriate guidance and learning strategies.